ASSESSMENT OF PREDICTIVE ACCURACY OF SOME AVEMENT TRANSVERSE DEFORMATION MODELS - Chazairin, Ronny
The Cianjur-Ciawi and Cirebon-Losari road links located in West Java encompass a wide range of topographical, geometric and traffic conditions, the former passing through steep hilly country and the latter through the flat North Java plain. These different factors influence vehicle speeds and the amount of charinelisatiori on the pavement which takes place. Excessive permanent deformation in highways can create a serious safety hazard and it can accelerate structural deterioration. In order to rationally design flexible pavements, in term of economics, safety, serviceability to the user, and structural damage, it is necessary to be able to predict the actual magnitude of permanent deformation under any given set of conditions. Various prediction models have been examined to determine permanent deformations of the above road links. The HILL and Van de LOO (1974) model which was adopted in the Shell pavement design manual {1978) analyses the rutting test in a manner that allows comparison to be made directly with the results of creep tests carried out under constant-load uniaxial compression conditions. Secondly, the ALLEN and BEEN (1986) model was tried; this analyses unconfined repeated-load tests performed on an asphaltic concrete mixture to predict accumulation of rutting in the field under repeated service loads. Finally the World Bank (PATERSON, 1987) empirical approach, based on the Brazil-UNDP study to estimate rut depth progression, was applied. The accuracy of the prediction procedure for in-situ permanent deformation depends to a large extent on that of the laboratory materials characterization tests, as well as the detailed manner in which the results of these are applied. Detailed data on field performance, traffic volumes and loads, pavement construction, and bituminous mix properties exist in TRRL and Pusat Penelitian dan Pengembangan Jalan Bandung, and which were collected as part of the IBRD VI Betterment Programme. These were provided as a basis of comparing field data with the model predictions. Prediction of permanent deformation results using the HILL and Van de LOO and The World Bank models showed fair agreement with the measured Garut depth on the Cianjur-Ciawi and Cirebon Losari road links. This was not found for the ALLEN and DEEN model.